The Style and Structure of Cultures in Organizations: Three Perspectives - Martin, Joanne (Organization Science, 1995)
Organizational culture is a topic that has brought to the surface fundamental theoretical, methodological, epistemological, and political disagreements. Such disagreements could be fruitful for this topic area and for the field of organizational studies, more broadly defined. Unfortunately, all too often, disagreements among cultural researchers take the form of a debate about which theory or method is the “one best way”: an open or unspoken struggle for intellectual dominance. When opposing points of view clash openly, assumptions are laid bare and declared unwarranted or foolish and alternate viewpoints are dismissed as misguided, empirically unfounded, or irrelevant to more important questions. In other kinds of papers, only a careful reading between the lines reveals the silencing of opposing points of view, as assumptions remain unstated or unchallenged and opposing points of view are omitted, marginalized in a footnote or an aside, or declared outside the paper’s focus. If culture were a topic area where quantitative methods were used by all, and if these disagreements were purely theoretical, a classic experiment or comprehensive archival study might be able to prove, conclusively, that a particular argument is false. However, because so much culture research is qualitative, such definitive empirical answers are unlikely, and so the culture debates become even less tolerant of opposing views.